A Evaluating DeepL as A Translation Tool: Facilitating or Hindering for EFL Students’ Language Acquisition - Nailatul Fitroh; Nuna Mustikawati Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Second Language Acquisition (SLA) is influenced by various tools, including machine translation (MT). Theories such as Krashen's Input Hypothesis highlight the role of comprehensible input in language learning, with recent studies demonstrating mixed effects of MT tools. Although MT tools like DeepL show potential, their impact on EFL students' abilities remains underexplored, particularly in writing and grammar. This study aims to evaluate the effects of DeepL on EFL students' language acquisition, focusing on their perceptions of how the tool helps or hinders their learning. A qualitative case study approach was used, involving semi-structured interviews with three EFL students who have used DeepL in their academic activities. The results indicate that DeepL facilitates comprehension and vocabulary acquisition, but if used excessively and without creating self-reflection, it can become a dependency that hinders independent language production. While DeepL is beneficial for language learning, it should be used as a complementary tool to prevent over-reliance and encourage deeper engagement with language practice. This study contributes to the understanding of the dual impact of translation tools in language education.